2013
DOI: 10.21082/ijas.v14n2.2013.p79-86
|View full text |Cite
|
Sign up to set email alerts
|

DIRECT AND INDIRECT SOMATIC EMBRYOGENESIS ON ARABICA COFFEE (Coffea arabica)

Abstract: Propagation of Coffea arabica L. through direct and indirect somatic embryogenesis technique is promising for producing large number of coffee seedlings. The objectives of the research were to evaluate methods for direct and indirect somatic embryo-genesis induction of C. arabica var. Kartika. The explants were the youngest fully expanded leaves of arabica coffee. The evalu-ated medium was modified Murashige and Skoog (MS) medium supplemented with a combination of 2.26 µM 2,4-D + 4.54 or 9.08 µM thidiazuron; 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 7 publications
0
8
0
13
Order By: Relevance
“…Kombinasi ZPT 2,4-dichlorophenoxyacetic acid (2,4-D) dengan 6-(y,ydimethylallylamino) purine (2-iP) telah digunakan sebelumnya oleh Ibrahim, Hartati, Rubiyo, Purwito, & Sudarsono (2015) (Murni, 2010) dan kopi Arabika (Ibrahim, Sudarsono, Syafaruddin, & Rubiyo, 2012). Kombinasi 2,4-D dan BAP pada kopi Arabika (Ibrahim, Hartati, Rubiyo, Purwito, & Sudarsono, 2013b), serta kombinasi antara 2,4-D dan thidiazuron pada kopi Arabika (Ibrahim, Hartati, Rubiyo, Purwito, & Sudarsono, 2013a;Ibrahim et al, 2015).…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Kombinasi ZPT 2,4-dichlorophenoxyacetic acid (2,4-D) dengan 6-(y,ydimethylallylamino) purine (2-iP) telah digunakan sebelumnya oleh Ibrahim, Hartati, Rubiyo, Purwito, & Sudarsono (2015) (Murni, 2010) dan kopi Arabika (Ibrahim, Sudarsono, Syafaruddin, & Rubiyo, 2012). Kombinasi 2,4-D dan BAP pada kopi Arabika (Ibrahim, Hartati, Rubiyo, Purwito, & Sudarsono, 2013b), serta kombinasi antara 2,4-D dan thidiazuron pada kopi Arabika (Ibrahim, Hartati, Rubiyo, Purwito, & Sudarsono, 2013a;Ibrahim et al, 2015).…”
Section: Pendahuluanunclassified
“…Berdasarkan hasil penelitian terdahulu, diketahui bahwa tingkat keberhasilan dalam menginduksi kalus embriogenik pada proses embriogenesis somatik tidak langsung pada kopi dipengaruhi oleh genotipe tanaman serta konsentrasi ZPT yang ditambahkan pada media induksi kalus tahap awal (Ibrahim et al, 2015). Di sisi lain, penelitian sebelumnya menunjukkan bahwa kalus muncul dari bekas sayatan daun (Ibrahim et al, 2013a;Ibrahim et al, 2015) sehingga dalam upaya meningkatkan persentase keberhasilannya perlu dilakukan penelitian lanjutan dengan menambah bidang sayatan pada eksplan yang telah steril. Di samping itu, untuk meningkatkan daya perkecambahan, dilakukan penambahan GA 3 yang diketahui dapat menambah jumlah embrio berkecambah dalam medium regenerasi.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…In spite of a great number of studies on the micropropagation of C. arabica by somatic embryogenesis (Söndahl and Sharp 1976;Yasuda et al 1985;Neuenschwander and Baumann 1992;Fuentes-Cerda et al 2001;Ahmed et al 2013;Ibrahim et al 2013;Lubabali et al 2014), there is only a dearth of information on the mechanisms that regulate the process of somatic embryogenesis at different stages. Roowiet al (2010) suggested that growth and development…”
Section: Introductionmentioning
confidence: 99%